[tex]Solution,solve\:for\:h,\:3h=7\left(\frac{2}{7}-\frac{3}{7}h\right)-10\quad :\quad h=-\frac{4}{3}[/tex]
[tex]Steps:[/tex]
[tex]3h=7\left(\frac{2}{7}-\frac{3}{7}h\right)-10[/tex]
[tex]\mathrm{Expand\:}7\left(\frac{2}{7}-\frac{3}{7}h\right)-10:\quad -3h-8, 3h=-3h-8[/tex]
[tex]\mathrm{Add\:}3h\mathrm{\:to\:both\:sides}, 3h+3h=-3h-8+3h[/tex]
[tex]\mathrm{Simplify}, 6h=-8[/tex]
[tex]\mathrm{Divide\:both\:sides\:by\:}6, \frac{6h}{6}=\frac{-8}{6}[/tex]
[tex]\mathrm{Simplify}, h=-\frac{4}{3}[/tex]
[tex]\mathrm{The\:Correct\:Answer\:Is\:h=-\frac{4}{3}}[/tex]
[tex]\mathrm{Hope\:This\:Helps!!!}[/tex]